CeO2 nanoparticles attenuate airway mucus secretion induced by TiO2 nanoparticles - Tsai, Shih-Ming; Duran-Robles, Edith; Goshia, Tyler; Mesina, Maria; Garcia, Carlos; Young, Julia; Sibal, Angelo; Chiu, Meng-Hsuen; Chin, Wei-Chun (The Science of the total environment, 2018)
Nanotoxicity studies associated with various nanoparticles (NPs) have attracted intense research interest due to the broader applications of nanoparticles in our daily lives. The exposure of nanoparticles can lead to hypersecretion and accumulation of airway mucus which are closely associated with many respiratory diseases. Titanium dioxide (TiO2), one of the PM10 components, is a major NP that is widely utilized in many commercial products. Our previous study established the connection between induced airway mucus secretion and TiO2 NPs. However, the countermeasure to reduce the harmful effects of TiO2 NPs, especially airway mucus secretion, remains unexplored. One of the potential candidates to reduce airway mucus secretion is cerium oxide (CeO2) NPs. It has been reported that CeO2 NPs can protect cells by diminishing ROS and inflammatory responses. Herein, our study shows that CeO2 NPs are able to reduce cytosolic Ca2+ changes and mitochondrial damage caused by TiO2 NPs. Our results provide the evidence that hypersecretion of mucus and apoptosis progression induced by TiO2 NPs can be attenuated by CeO2 NPs. This study highlights the potential capacity of CeO2 NPs as a supplementary material for TiO2 NPs applications in the future. [Display omitted] •CeO2 NPs attenuate the toxicity effect caused by TiO2 NPs.•Cytosolic Ca2+ change and mucus secretion can be diminished by CeO2 NPs.•CeO2 NPs inhibit BEAS-2B cell apoptosis progression.